Strategy for Optimizing Effa Design's Tiktok Content to Increase Engagement Rate - Syarifah Fadhilah; Siti Nurjanah (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
In the digital era, TikTok has become a vital tool for business promotion with over 1 billion active users. The "Effa Design" TikTok account, focusing on graphic design, has 31,200 followers and an Engagement Rate (ER) of 5.25%. Despite this, increasing the ER remains a priority. Key strategies include content quality, posting consistency, follower interaction, hashtag usage, and trend following. Challenges include TikTok's algorithm, competition, and rapid trend changes. This qualitative case study aims to identify effective strategies to boost the ER of "Effa Design." Data were collected from the account owner, TikTok experts, and followers through interviews, observation, and documentation, and validated using triangulation. Analysis revealed strategies like niche consistency, content variation, hooks, active interaction, relevant hashtags, and personal branding. Interviews emphasized consistent, relevant content and routine evaluations based on TikTok insights. The CESM Framework was applied, focusing on building trust and commitment, enhancing customer engagement through satisfaction and positive emotions, and considering behavioral intentions, WOM, and performance.